Transoral laser microsurgery of benign and malignant lesions - Bernal-Sprekelsen, Manuel; ilaseca, Isabel (Thieme, 2016)
This state-of-the-art book is an invaluable resource for surgeons because it covers not only the equipment and surgical aspects but, very importantly for decision making, it also provides site-specific evidence for the use of TLM in the treatment of benign disorders and malignant disease, even at advanced stages